Integrated System for Evaluation of Implementation of Internal Quality Audits and ISO 9001; 2015 Case Study : Universitas Pembangunan Nasional “Veteran” Jawa Timur - Mohammad Idhom; Jojok Dwiridotjahjono; I Gede Susrama Mas Diyasa; Rheza Rizqi Ahmadi; Munoto (Internasional Journal of Data Science, Engineering, and Anaylitics, 2021)
The Internal Quality Assurance System (SPMI) is a system to ensure quality in the process of providing education. All components in the process of providing education support the achievement of aspects of SPMI. An important role in SPMI is the scope of the study program (Prodi), faculties, Institute for Learning Development and Quality Assurance (LP3M), and reviewers. Study program/faculty as SPMI document compiler. LP3M acts as system manager and decision maker at SPMI. Reviewers as assessors who assess the results of the SPMI study program documents. In SPMI activities, study programs / faculties fill out the required form files. Then the reviewer can evaluate the completed file with a score from 1 to 4. However, the evaluation process which is also called Internal Quality Audit (AMI) is still manual. This makes it less easy for LP3M managers to monitor evaluation values ​​and make decisions. From the description above, this proposal proposes a system that can perform an integrated evaluation of AMI online. Not only focusing on AMI, SITEPAMIS can also conduct evaluations to meet ISO 9000;2015. ISO 9000;2015 is a standard for quality management. This research is divided into two years. In the first year, the creation of a web technology-based system with evaluation features of AMI and ISO 9000;2015 values ​​until the implementation process. The output of this stage is a SITEPAMIS web application, reputable national journals, national seminars, and copyrights. In the second year, the mobile version of SITEPAMIS was started. The output of this stage is a SITEPAMIS mobile application, international journals, international seminars, and textbooks, so that at the end of the research results in an Integrated System Application for Evaluation of Internal Quality Audit Implementation and an ISO version of SITEPAMIS which is purely Web-based.